Sensory analysis of foods of animal origin - Toldra, Fidel (CRC Press/Taylor & Francis, 2011)
Devoted specifically to the analysis of sensory parameters in food products of animal origin, this book describes the main analytical techniques and methodologies and their application. It describes the analysis of color and texture, including advances texture measuring